Purification of recombinant endoglucanase GH5-CBM72-CBM72 expressed in Escherichia coli - Thi Dung, Cao; Trong Khoa, Dao; Quy, Nguyen Thi; Huyen Thi, Do; Nam Hai, Truong (Academia Journal of Biology, 2022)
In a previous study, a gene GL0694641 coding for endoglucanase containing 3 domains GH5-CBM72-CBM72 was exploited from metagenomic DNA data of bacteria in Vietnamese goats’ rumen. The gene (eg5) encoding the mature enzyme (without signal peptide coding sequence) was optimized codons, artificially synthesized, and inserted into the pET22b(+) vector at NcoI and XhoI to generate expression vector pET22-eg5 for expression of the gene in Eschrichia coli. In this study, the gene eg5 was well expressed in E. coli BL21 and Rosetta 1 strains to produce recombinant endoglucanase of 77 kDa. The recombinant enzymes were expressed mainly in the soluble fractions of both strains. However, the enzyme expressed in E. coli BL21 was precipitated by imidazole at even a low concentration of 20 mM, whereas endoglucanase produced from E. coli Rosetta 1 strain was well soluble in buffers containing imidazole at concentrations of 20, 50, 200, and 250 mM. To our knowledge, this is the first study showing the negative effect of imidazole on recombinant protein. Endoglucanase expressed from strain E. coli Rosetta 1 was successfully purified by His-tag affinity chromatography using phosphate buffer saline (PBS). Protein contaminations were washed out by PBS buffer containing 20 mM and 75 mM imidazole then the target protein was harvested by the buffer containing 200 mM imidazole. After purification and desalting by the PD10 column, the recombinant endoglucanase had purity up to 97%. The pure enzyme exhibited endoglucanase activity hydrolyzing carboxymethyl cellulose in agar plate and by zymogram. The purified enzyme can be used as a material for its characterization.